Peranan Pemerintah Nagari dalam Mengatasi Kemiskinan di Nagari Sisawah Kecamatan Sumpur Kudus Kabupaten Sijunjung - Elda Nengsri; Jamurin Jamurin; Indra Rahmat (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study aims to elucidate the determinants of impoverished conditions and analyze the proactive role of the Nagari Government in mitigating destitution within Nagari Sisawah, situated in the Sumpur Kudus District of Sijunjung Regency. Employing a qualitative approach with descriptive techniques, this research centers on key participants including Nagari leaders, officials, and the local community. The study's findings reveal that the origins of poverty within Nagari Sisawah encompass several factors, including insufficient economic returns from rubber cultivation for sustaining families, the repercussions of the Covid-19 pandemic, and constrained employment prospects due to limited educational attainment. The Nagari government has made various efforts to overcome poverty, namely providing socialization and information on economic activities to the community, assisting the community in making proposals to obtain superior seeds and providing assistance to the community through various programs such as PKH and Direct Funding for the community.